The Influence of Service Quality on Passenger Satisfaction At Pt. Pelni Murhum Baubau - Ismawati, Ismawati (Institute for Research and Community Service, 2022)
The purpose of this study is to determine and analyze the effect of service quality on passenger satisfaction of PT. PELNI Murhum Baubau port. The sample is determined by using the Slovin formula. Methods of data collection using a questionnaire. The data analysis method is simple linear regression analysis. The data instrument test uses validity, reliability, coefficient of determination test and partial t test. Based on the results of the data in this study, all data were declared valid and reliable. The conclusion that can be drawn is the result of the value of Tcount (7.701)> Ttable (2.010) and the significant value is less than 0.05, then H0 is rejected and Ha is accepted. This means that service quality has a positive and significant effect on passenger satisfaction. The value of R Square is 0.937 which indicates that the Y variable, namely passenger satisfaction, is strongly influenced by the X variable by 93.7% and the rest is influenced by other dimensions that are not investigated further in this study.